Pretransplant Opioid Use and Survival After Lung Transplantation. Issue 8 (August 2020) - Vahidy, Sana; Li, David; Hirji, Alim; Kapasi, Ali; Weinkauf, Justin; Laing, Bryce; Lien, Dale; Halloran, Kieran
Abstract : Background: The impact of opioid use in lung transplant candidates on posttransplant outcomes is unknown. Studies on opioid therapy in kidney and liver transplant candidates have suggested increased risk of graft failure or death. We sought to analyze the relationship between pretransplant opioid use in lung transplant candidates and retransplant-free survival. Methods: We retrospectively reviewed adult patients transplanted consecutively between November 2004 and August 2015. The exposure was any opioid use at time of transplant listing and primary outcome was retransplant-free survival, analyzed via Cox regression model adjusted for recipient age, gender, ethnicity, diagnosis, and bridging status. Secondary outcomes included duration of ventilation, intensive care unit and hospital length of stay, 3-month and 1-year survival, continuing opioid use at 1 year, and time to onset of chronic lung allograft dysfunction. Results: The prevalence of opioid use at time of listing was 14% (61/425). Median daily oral morphine equivalent dose was 31 mg (18–54). Recipient ethnicity was associated with pretransplant opioid use. Opioid use at time of listing did not increase risk of death or retransplantation in an adjusted model (hazard ratio 1.12 [95% confidence interval 0.65-1.83], P = 0.6570). Secondary outcomes were similar between groups except hospital length of stay (opioid users 35 versus nonusers 27 d, P = 0.014). Continued opioid use at 1-year posttransplant was common (27/56, 48%). Conclusions: Pretransplant opioid use was not associated with retransplant-free survival in our cohort and should not necessarily preclude listing. Further work stratifying opioid use by indication and the association with opioid use disorder would be worthwhile.